The Relationship Between the Triple Airway Maneuver Insertion Technique and The Success Rate of Laryngeal Mask Airway Installation in Elective Surgery - Bagas Kara Alfaridzi; Asmat Burhan; Feti Kumala Dewi (Java Nursing Journal, 2024)
Background: The Laryngeal Mask Airway (LMA) is a widely utilized supraglottic airway device by anesthesiologists in selective procedures, particularly in cases where intubation is not feasible or when managing a difficult airway. Complicating factors such as a short neck and large tongue can hinder LMA insertion, necessitating the use of the Triple Airway Maneuver (TAM). This technique involves a combination of head elevation, anterior mandible lift, and mouth opening to facilitate airway clearance. Purpose: This study was to evaluate the relationship between the TAM technique and the success rate of LMA insertion during elective surgeries at Dr. Soedirman Kebumen General Hospital. Methods: A cross-sectional, analytic study was conducted in June 2024, involving 52 respondents selected via purposive sampling. Data were collected using observation sheets. Findings: The findings revealed that the majority of respondents were aged 17-25 years (38.5%) and had a body mass index of 18.5-25.0 (73.1%). Non-smokers constituted 73.1% of the sample, while 46.2% had occupations involving repetitive neck movements. The TAM group achieved 45 successful LMA insertions, with 44 succeeding on the first attempt and 1 on the second, compared to 7 successful insertions in the non-TAM group. However, Kendall’s tau c test (p=0.056) indicated no statistically significant relationship between TAM and LMA insertion success rates, and the correlation coefficient (0.385) suggested a weak relationship. Conclusions: the TAM technique does not significantly influence the success rate of LMA insertion